2013
DOI: 10.1093/nar/gkt178
|View full text |Cite
|
Sign up to set email alerts
|

Translating mRNAs strongly correlate to proteins in a multivariate manner and their translation ratios are phenotype specific

Abstract: As a well-known phenomenon, total mRNAs poorly correlate to proteins in their abundances as reported. Recent findings calculated with bivariate models suggested even poorer such correlation, whereas focusing on the translating mRNAs (ribosome nascent-chain complex-bound mRNAs, RNC-mRNAs) subset. In this study, we analysed the relative abundances of mRNAs, RNC-mRNAs and proteins on genome-wide scale, comparing human lung cancer A549 and H1299 cells with normal human bronchial epithelial (HBE) cells, respectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

11
257
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 174 publications
(273 citation statements)
references
References 51 publications
11
257
0
5
Order By: Relevance
“…Previous studies demonstrated the abundance of translating mRNAs correlated positively with that of proteins, but negatively with the length of mRNAs in tumor cells 32. Since the mRNAs for these five genes were relatively short, we then determined the possibility of using these five proteins to develop a novel predictive survival model.…”
Section: Survival‐related Genes Were Selected For Testingmentioning
confidence: 99%
“…Previous studies demonstrated the abundance of translating mRNAs correlated positively with that of proteins, but negatively with the length of mRNAs in tumor cells 32. Since the mRNAs for these five genes were relatively short, we then determined the possibility of using these five proteins to develop a novel predictive survival model.…”
Section: Survival‐related Genes Were Selected For Testingmentioning
confidence: 99%
“…However, transcriptome sequencing still has crucial drawbacks even with substantially developed nextgeneration sequencing techniques (NGS). Numerous studies have found untranslated mRNA species in various human cell lines [15][16][17][18], and these species comprise approximately 5% of the transcriptome [2,14]. Transcriptome sequencing does not distinguish the translating and untranslated RNA.…”
mentioning
confidence: 99%
“…To correct the possible annotation errors in genome and to discover new proteins, we proposed a new strategy that analyzes the translating mRNA (translatome sequencing) to find the translating evidence of known and unknown coding genes [14,19]. It is known that proteins are synthesized via translation, therefore the translating evidence of proteins, obtained by translatome sequencing and sequence analysis, can be a sensitive method to find new proteins.…”
mentioning
confidence: 99%
See 2 more Smart Citations